Effect of C and N and their absence on the kinetics of austenite-ferrite phase transformations in Fe-0.5Mn alloy. (15th May 2018) - Farahani, Hussein; Zurob, Hatem; Hutchinson, Christopher R.; van der Zwaag, Sybrand
Abstract: Investigating the partitioning effect of substitutional and interstitial elements on the migration of transformation interfaces during austenite-ferrite phase transformation in steels with the conventional experimental method is extremely challenging due to interaction between the solute atoms and the transformation interfaces. Additionally, the simultaneous nucleation of new phases during phase transformations limits the accuracy of extracted growth rates from experimental kinetics measurements of phase fractions. In a novel experimental approach, the cyclic partial phase transformation concept is used to avoid the effect of nucleation on total kinetics of phase transformations. In this study, a Fe-0.5Mn alloy in the presence and absence of interstitial C and N additions is subjected to different cyclic transformation routes to examine the possible interaction between solute atoms and migrating interfaces. The experimental results are in semi-quantitative agreement with modelling predictions made by the local equilibrium approach and provide indirect evidence of Mn partitioning at austenite/ferrite interface in absence of any interstitial elements. It is also confirmed that the presence of interstitial elements promotes Mn interaction with the interface, whereas N promotes more Mn partitioning at transformation interface compared to C. Graphical abstract: Image 1